Aramid nanofiber-based carbonaceous aerogel and preparation method thereof
By adjusting the degree of hydrolysis of aramid fibers and using vacuum suction filtration to prepare aramid nanofiber-based carbon aerogels, forming a slit-shaped pore structure, and performing hydrophobic treatment, the problems of excessive aerogel pore size and influence of clear water layer in the prior art are solved, and efficient photothermal conversion and stable seawater desalination effects are achieved.
Patent Information
- Application Number
- CN202411458336.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the aerogel pore size is too large and the influence of the clear water layer is not considered, resulting in a low thermal conversion efficiency of the aerogel.
Aramid nanofiber-based carbon aerogel was prepared by adjusting the degree of hydrolysis of aramid fibers and using vacuum suction filtration to form a slit-shaped pore structure, and hydrophobic treatment was performed on the upper surface of the aerogel to avoid the formation of a clear water layer.
有效提高了气凝胶的蒸发效果,减少了热损伤,提高了光热转换效率,并增强了在海水中的稳定性。
Smart Images

Figure CN119503765A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of interface evaporation, in particular to an aramid nanofiber-based carbon aerogel and a preparation method thereof. Background Art
[0002] With the growth of the earth's population and the increasing demand for water resources in agriculture and industry, water shortage has become one of the major challenges of modern society. Although 70.8% of the earth's surface is covered by water, 97.5% of the water is not directly drinkable, and the self-purification capacity of freshwater bodies is declining. Therefore, it is very valuable to establish efficient water purification technology to produce fresh water. In the past decade, interfacial photothermal evaporation technology has received widespread attention and has developed rapidly. For an ideal solar-driven interfacial evaporator, effective light absorption, reasonable thermal management capabilities, and barrier-free water transport and evaporation channels are required. The completion of the above-mentioned urgent problems under the joint action of materials and structures has far-reaching significance for the acquisition of freshwater resources.
[0003] In the interfacial evaporator, the performance of photothermal materials is crucial. At present, the commonly used photothermal conversion materials are mainly precious metal materials, polymer materials, semiconductor materials, carbon-based materials, etc. Among them, carbon-based materials have attracted widespread attention due to their low cost, simple acquisition method, excellent stability and wide spectral absorption range. In the form of interfacial evaporators, aerogel materials have attracted widespread attention due to their extremely low density, rich pores, good heat management ability and other advantages. The aerogel interfacial evaporator currently used is to construct the pores of aerogels by ice template method, radial freezing method and other methods, but these methods easily lead to excessive aerogel pores. Excessive pores lead to strong water convection, which inevitably increases the heat loss of the interfacial evaporation system to the water body, resulting in reduced efficiency; on the other hand, according to the Laplace equation, the larger the pore size, the less conducive to capillary action, and it is impossible to quickly supply water to the water vapor interface, thus limiting the shortcomings of actual large-scale application. In practical applications, the upper surface clear water layer will affect the rate of interfacial evaporation. For example, patent CN118005126A proposes a low-tortuosity layered stepped pore structure aerogel interface evaporation device, but the device does not consider the effect of the upper surface clear water layer on the light absorption performance of the photothermal material during actual use. Patent CN118125540A proposes a three-layer biomass-based carbon aerogel evaporator, using lignin carbon quantum dots / chitosan carbon aerogel evaporation material as the upper layer of the solar evaporator, absorbent paper tape as the middle transition layer, and polystyrene foam as the lower layer. However, the aerogel part of the interface evaporator has not been structurally designed and is formed using the ice template method, which easily leaves large-diameter channels. In addition, plastic cups are used for freeze-forming without directional freezing, and the direction of the channels is chaotic, which further affects the transmission rate of water to the interface. The more aerogel materials are superimposed, the more significant the adverse effects become. Patent CN118047438A proposes an expanded perlite-based aerogel structure solar interface evaporator. Although it adopts directional freezing, it still has the problem of large diameter channels after ice template molding mentioned above, and also does not consider the influence of the open water layer in actual application. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem in the prior art that the aerogel pore size is too large and the influence of the clear water layer is not considered, resulting in low thermal conversion efficiency of the aerogel.
[0005] In order to solve the above technical problems, the present invention provides an aramid nanofiber-based carbon aerogel and a preparation method thereof. The present invention adjusts the degree of hydrolysis of aramid fibers and adopts a vacuum filtration method to prepare aramid nanofiber-based carbon aerogel. Since the aramid nanofibers aggregate through hydrogen bonds to form sheet fibers, when filtered under external pressure, the sheet fibers adhere to each other to form a slit-type pore structure. The pore diameter obtained by vacuum filtration is smaller, so more pores are provided per unit area, and the abundant voids give the aerogel a better evaporation effect. In addition, hydrophobic treatment on the upper surface of the aerogel can avoid the problem of a clear water layer at the gas-liquid interface during use, which leads to a decrease in the photothermal evaporation effect of the aerogel.
[0006] The first object of the present invention is to provide a method for preparing aramid nanofiber-based carbon aerogel, comprising the following steps:
[0007] S1, dispersing aramid fibers in an alkaline solution, performing a deprotonation treatment, and dispersing to obtain a mixture containing aramid nanofibers; washing the mixture containing aramid nanofibers with deionized water to obtain an aramid nanofiber dispersion;
[0008] S2, vacuum filtering the aramid dispersion and freeze-drying to obtain aramid nanofiber aerogel;
[0009] S3, carbonizing the aramid nanofiber aerogel to obtain the aramid nanofiber-based carbonaceous aerogel.
[0010] Furthermore, the mass concentration of the aramid dispersion in step S1 is 3-7 mg / mL.
[0011] Furthermore, the volume ratio of the mass of the alkali to the cosolvent in the alkaline solution is (1-2) g: 100 mL. The aramid fiber is treated in an alkali (such as potassium hydroxide KOH) and a cosolvent (such as dimethyl sulfoxide DMSO) to remove the hydrogen on the amide bond to form a negatively charged polyanion, which is then dissolved in DMSO to form an aramid nanofiber dispersion. Potassium hydroxide can enhance the deprotonation ability of aramid, making the aramid molecular chain easier to open and dissolve, which helps to improve the uniformity of the fibers in the solution, thereby preparing more uniform nanofibers. The mixed solution of potassium hydroxide and dimethyl sulfoxide will affect the morphology of the aramid fibers, thereby affecting the pore size between the aramid fibers during the vacuum filtration process, and ultimately affecting the evaporation efficiency of the entire aerogel.
[0012] In step S1, the base is selected from one or more of potassium hydroxide and sodium hydroxide, and the cosolvent is selected from one or more of dimethyl sulfoxide, acetone, ethanol, methanol, tetrahydrofuran, acetonitrile, ethyl acetate, pyridine, glycerol, polyethylene glycol, and cyclohexane.
[0013] Furthermore, the mass ratio of the aramid to the alkali in step S1 is (0.1-0.5): 1.5. The ratio of aramid to alkali affects the degree of hydrolysis of the aramid fiber. When the degree of decomposition of the aramid fiber is too large, the diameter of the aramid nanofiber is too thin, the thermal stability becomes poor, and some pores collapse and merge into large pores during the carbonization process, resulting in a decrease in specific surface area. At the same time, when there is more aramid, the specific surface area of the aerogel will also decrease due to the larger fiber diameter.
[0014] Furthermore, the reagent used for washing in step S1 is deionized water. Deionized water can react with the polyanion in the aramid nanofiber dispersion to make the amide bond regain protons and form hydrogen bonds, thereby restoring the molecular structure of the aramid nanofiber. This is to avoid the precipitation and reagglomeration of the aramid nanofiber affecting its dispersibility and the performance of the final product.
[0015] Furthermore, the vacuum degree of the vacuum filtration in step S2 is 0.01-0.1Mpa, and the pore size of the filter screen of the vacuum filtration is 400-600 mesh. The higher the vacuum degree, the faster the water removal, the tighter the fiber aggregation, the denser the gel but may be uneven; the lower the vacuum degree, the slower the water removal, the uniform but may be looser the gel. The smaller the pore size of the filter screen, the better the fiber retention, the denser the gel but the greater the filtration resistance; the larger the pore size, the faster the filtration, but the fiber may be lost, resulting in loose gel.
[0016] Furthermore, the freeze-drying temperature in step S2 is -40°C to 30°C, and the freeze-drying time is 60-80 hours.
[0017] Furthermore, the carbonization treatment in step S3 is carried out under an inert atmosphere, the temperature of the carbonization treatment is 700-1000° C., and the time of the carbonization treatment is 0.5-2 hours.
[0018] The second object of the present invention is to provide an aramid nanofiber-based carbon aerogel prepared by the above preparation method.
[0019] The third object of the present invention is to provide an interfacial evaporator, which includes the above-mentioned aramid nanofiber-based carbon aerogel, wherein the surface of the aramid nanofiber-based carbon aerogel in contact with the evaporating liquid is defined as a first surface, and the surface of the aramid nanofiber-based carbon aerogel away from the first surface is defined as a second surface, and the second surface is hydrophobically treated.
[0020] Furthermore, the hydrophobic treatment is to apply a hydrophobic agent on the second surface and heat cure at 70-90° C. for 1-3 hours.
[0021] Furthermore, the hydrophobic agent is selected from one or more of methyl perfluorododecanoate, perfluorooctane sulfonic acid, perfluorooctane carboxylic acid, perfluorononanoic acid, and perfluorohexane sulfonic acid.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention prepares aramid nanofiber-based carbon aerogel by using a vacuum filtration method, and designs the pore structure of the aerogel by regulating the degree of hydrolysis of the aramid fiber, thereby effectively avoiding the thermal damage caused by the large pore size due to the large volume of ice crystals caused by the ice template method, radial freezing method and other methods. In addition, the present invention performs a hydrophobic treatment on the upper surface of the aramid nanofiber-based carbon aerogel, effectively avoiding the defect of a clear water layer at the gas-liquid interface during actual use, which leads to a decrease in the photothermal evaporation effect of the product. On the other hand, the aramid nanofiber prepared by deprotonation in the present invention retains a series of excellent properties of aramid fiber, has good salt resistance, and can stably function in seawater.
[0024] (2) Compared with traditional seawater desalination technologies, such as reverse osmosis membrane method, distillation method and the like, the energy used in the present invention comes only from solar energy, with low equipment investment, low energy consumption and environmental friendliness.
[0025] (3) Compared with volumetric seawater desalination technology, the present invention can effectively gather heat at the air-water interface, effectively reduce heat loss, and improve photothermal conversion efficiency.
[0026] (4) Compared with two-dimensional interface evaporation devices such as membrane type, the product of the present invention is highly controllable and can effectively obtain energy from the surrounding environment to increase the overall evaporation rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein
[0028] Figure 1 Schematic diagram of the preparation method of aramid nanofiber-based carbon aerogel; in the figure: 1-vacuum filtration, 2-freeze drying, 3-carbonization, 4-hydrophobic treatment;
[0029] Figure 2 It is a diagram showing the lightweight effect of aramid nanofiber-based carbon aerogel and a schematic diagram of its slit structure;
[0030] Figure 3 It is the evaporation rate comparison curve. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0032] like Figure 2As shown, the present invention is a black three-dimensional block material in appearance, and has a slit-type pore structure inside. The raw material of the aerogel is aramid fiber, which is deprotonated to form aramid nanofibers, and the aramid nanofiber aerogel is obtained by vacuum filtration and freeze drying, and then carbonized to obtain the aramid nanofiber-based carbon aerogel of the present invention. Among them, the hydrophobic layer is only located on the upper surface of the aerogel, and its thickness does not exceed 1μm.
[0033] like Figure 1 As shown, in the present invention, a vacuum filtration method is used in the preparation process of aramid nanofiber-based carbon aerogel. The principle is to rely on the abundant hydrogen bonds between aramid nanofibers to aggregate into sheet-like fibers. When filtration is performed under external pressure, the sheet-like fiber membranes are assembled and stacked layer by layer to form a Figure 2 The layered structure shown in the figure. The internal sheet-like fibers of the aerogel prepared by this method adhere to each other to form a slit-type pore structure. Compared with the large-diameter pores of aerogel prepared by the ice template method, the pores obtained by the vacuum filtration method have a smaller diameter, thus providing more pores per unit area. The rich pores give the aerogel a lightweight property, with a density of about 14 mg / cm 3 Much smaller than the density of water 1g / cm 3 Its floatability meets the requirements of interface heating in the interface evaporation system.
[0034] In the present invention, unless otherwise specified, the materials used in the following examples can be obtained from commercial sources.
[0035] In the present invention, unless otherwise specified, the purity of aramid fibers (ANFs) is AR, which is purchased from Yantai Taihe New Materials Company.
[0036] In the present invention, unless otherwise specified, the purity of sodium hydroxide is AR, which is purchased from Aladdin Reagent (China) Co., Ltd.
[0037] In the present invention, unless otherwise specified, the purity of dimethyl sulfoxide is AR, which is purchased from Aladdin Reagent (China) Co., Ltd.
[0038] In the present invention, unless otherwise specified, the purity of methyl perfluorododecanoate is AR, which is purchased from Aladdin Reagent (China) Co., Ltd.
[0039] Example 1
[0040] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0041] Step (1): Preparation of aramid nanofiber dispersion
[0042] The aramid filaments were cut into short fibers of about 5 mm in length. After removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 h to obtain a deep red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0043] Step (2): Preparation of aramid nanofiber aerogel
[0044] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0045] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0046] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0047] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0048] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0049] Example 2
[0050] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0051] Step (1): Preparation of aramid nanofiber dispersion
[0052] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0053] Step (2): Preparation of aramid nanofiber aerogel
[0054] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0055] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0056] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 800°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0057] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0058] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0059] Example 3
[0060] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0061] Step (1): Preparation of aramid nanofiber dispersion
[0062] Cut the aramid filament into short fibers of about 5 mm in length, remove impurities on the fiber surface, take 0.2g of aramid and disperse it in a mixed solution of 1.5g potassium hydroxide and 100mL of dimethyl sulfoxide, add 4% deionized water, and stir at room temperature for about 4h to obtain a dark red ANFs mixed solution (2mg / mL). Take 100mL of the ANFs mixed solution, add 100mL of deionized water under stirring to reduce it, wash it several times and filter it to obtain a 5mg / mL ANFs dispersion.
[0063] Step (2): Preparation of aramid nanofiber aerogel
[0064] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0065] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0066] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 600°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0067] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0068] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0069] Example 4
[0070] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, comprising the following steps:
[0071] Step (1): Preparation of aramid nanofiber dispersion
[0072] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 3 mg / mL ANFs dispersion was obtained.
[0073] Step (2): Preparation of aramid nanofiber aerogel
[0074] The 3 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0075] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0076] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0077] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0078] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0079] Example 5
[0080] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0081] Step (1): Preparation of aramid nanofiber dispersion
[0082] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 7 mg / mL ANFs dispersion was obtained.
[0083] Step (2): Preparation of aramid nanofiber aerogel
[0084] The 7 mg / mL ANFs dispersion was transferred to a mold and filtered to form a 1 cm high cylindrical hydrogel; it was quickly frozen with liquid nitrogen and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa).
[0085] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0086] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0087] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0088] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0089] Example 6
[0090] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0091] Step (1): Preparation of aramid nanofiber dispersion
[0092] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.4 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 200 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0093] Step (2): Preparation of aramid nanofiber aerogel
[0094] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0095] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0096] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0097] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0098] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0099] Example 7
[0100] This embodiment provides a method for preparing aramid nanofiber-based carbon aerogel, which specifically includes the following steps:
[0101] Step (1): Preparation of aramid nanofiber dispersion
[0102] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.1 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 50 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0103] Step (2): Preparation of aramid nanofiber aerogel
[0104] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0105] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0106] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0107] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0108] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0109] Comparative Example 1
[0110] This comparative example is basically the same as Example 1, except that the aramid nanofiber aerogel is not carbonized. The specific steps are as follows:
[0111] Step (1): Preparation of aramid nanofiber dispersion
[0112] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0113] Step (2): Preparation of aramid nanofiber aerogel
[0114] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0115] Step (3): Hydrophobic treatment of aramid nanofiber-based aerogel
[0116] The surface of the aramid nanofiber-based aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 s. The aerogel sample was then placed in an oven and thermally cured at 80 ° C for 2 h.
[0117] Comparative Example 2
[0118] This comparative example is basically the same as Example 1, except that the preparation method of aramid nanofiber-based carbon aerogel adopts directional freezing method, and the specific steps are as follows:
[0119] Step (1): Preparation of aramid nanofiber dispersion
[0120] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the aramid nanofiber mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0121] Step (2): Preparation of aramid nanofiber aerogel
[0122] The 5 mg / mL ANFs dispersion was transferred to a directional freezing device, liquid nitrogen was injected into the mold, and it was directionally frozen using a temperature gradient. Finally, aramid nanofiber aerogel (ANFAs) was obtained after freeze-drying for 72 hours to remove water.
[0123] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0124] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0125] Step (4): Hydrophobic treatment of aramid nanofiber-based carbon aerogel
[0126] The surface of the aramid nanofiber-based carbon aerogel sample was treated with hydrophobicity using a spray gun, using methyl perfluorododecanoate solution as a hydrophobic agent, adjusting the gas pressure to 50 psi, the spray distance to 40 cm, and the spray time to 30 seconds. The aramid nanofiber-based carbon aerogel sample was then placed in an oven and thermally cured at 80°C for 2 hours.
[0127] Comparative Example 3
[0128] This comparative example is basically the same as Example 1, except that the aramid nanofiber-based carbon aerogel is not subjected to hydrophobic treatment. The specific steps are as follows:
[0129] Step (1): Preparation of aramid nanofiber dispersion
[0130] The aramid filaments were cut into short fibers of about 5 mm in length, and after removing impurities from the fiber surface, 0.2 g of aramid was dispersed in a mixed solution of 1.5 g of potassium hydroxide and 100 mL of dimethyl sulfoxide, and 4% deionized water was added. The mixture was stirred at room temperature for about 4 hours to obtain a dark red ANFs mixed solution (2 mg / mL). 100 mL of the ANFs mixed solution was taken, and 100 mL of deionized water was added under stirring to reduce it. After multiple washings and filtration, a 5 mg / mL ANFs dispersion was obtained.
[0131] Step (2): Preparation of aramid nanofiber aerogel
[0132] The 5 mg / mL ANFs dispersion was transferred to a mold and filtered into a 1 cm high cylindrical hydrogel (filter mesh size 500 mesh, vacuum degree 0.05 MPa); it was quickly frozen into shape using liquid nitrogen, and finally freeze-dried for 72 hours to remove water to obtain aramid nanofiber aerogel.
[0133] Step (3): Preparation of aramid nanofiber-based carbon aerogel
[0134] Using inert atmosphere carbonization technology, the aramid nanofiber aerogel prepared in step (2) is placed in a tubular furnace, and N 2 , in N 2 The carbonization treatment was carried out by heating in an atmosphere for 1 h, and the carbonization temperature was set to 1000°C to obtain a black block of aramid nanofiber-based carbon aerogel.
[0135] The solar-driven interface evaporators prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested for absorbance, evaporation rate, and water transfer efficiency:
[0136] Absorbance test: The aramid nanofiber-based carbon aerogels prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were respectively placed in an ultraviolet spectrophotometer, and the integrating sphere mode was selected to measure the transmittance T% and the reflectance R% in the full spectrum band of 200-2500, thereby calculating the absorbance A=1-TR.
[0137] Specific surface area test: The specific surface area is measured by gas adsorption method. The equilibrium adsorption amount of gas on the surface of aramid nanofiber-based carbon aerogel prepared in Examples 1 to 7 and Comparative Examples 1 to 3 is measured, and the specific surface area is calculated by theoretical model. 2 Degassing treatment at 200 °C for 3 h in atmosphere, adsorption of N at 70 K 2 Conduct a test.
[0138] Evaporation rate test: The aramid nanofiber-based carbon aerogels prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were placed in containers filled with water, respectively, and suspended on the water surface. They were placed on an electronic balance and placed in a photochemical reaction box, and exposed to simulated sunlight under the condition of 1 sunlight. The electronic balance reading was read every 5 minutes, and the water mass and time curves of Examples 1 to 7 and Comparative Examples 1 to 3 within 300 minutes were plotted to calculate the evaporation rate.
[0139] Water transfer efficiency test: 20 mg / L methylene blue solution was prepared and placed in a container, and the aramid nanofiber-based carbon aerogels prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were placed in containers filled with methylene blue solution, respectively, and a white paper towel was placed on the upper surface of the solar-driven interface evaporator. The time from the aerogel being placed in the container to the paper towel turning blue was measured, and the water transfer efficiency was calculated. The results are shown in Table 1.
[0140] Table 1 Test results of Examples 1-7 and Comparative Examples 1-3
[0141]
[0142] Table 2 Comparison of water loss between Examples 1-7 and Comparative Examples 1-3
[0143]
[0144] It can be seen from the data in Table 1 that compared with Comparative Example 1, the absorbance and evaporation rate of Examples 1-7 are significantly improved, proving that carbonization can significantly enhance the evaporation effect of aerogels. Among them, the slit-type pore structure aramid nanofiber-based carbon aerogel prepared in Example 1 has greatly improved absorbance and evaporation rate compared with Comparative Example 1, with an absorbance of up to 96.8% and an evaporation rate of up to 3.42 Kg / m 2 h, the reason is that the carbonization treatment of Example 1 turns the originally light-colored aerogel into a black carbon material, thereby greatly improving its broad-spectrum absorption capacity for sunlight, significantly improving its absorbance and evaporation rate, and providing the necessary conditions for the application of the present invention in the field of interface evaporation. At the same time, Examples 1, 4, and 5 changed the concentration of the aqueous dispersion of ANFs, and found that the higher the content of aramid nanofibers, the higher the evaporation rate. The evaporation rate of the aerogel in Example 5 was slightly lower than that in Examples 1 and 4, which may be because as the content of aramid nanofibers increased, a dense and disordered agglomerate structure was formed during the self-assembly process, and the number of pores decreased.
[0145] It can be seen from the data in Table 1 that the aramid nanofiber-based carbon aerogel prepared in Example 1 has greatly improved evaporation rate and water transfer efficiency compared with Comparative Example 2, with the water transfer efficiency reaching 1.11 cm / s and the evaporation rate reaching 3.42 kg / m 2 h. The reason is that in Example 1, a vacuum filtration method is used to prepare the aramid nanofiber aerogel, and the abundant hydrogen bonds between the aramid nanofibers are used to aggregate into sheet fibers. When filtered under external pressure, the sheet fiber membranes are assembled and stacked layer by layer. The sheet fibers inside the aerogel prepared by this method adhere to each other to form a slit-type pore structure. Compared with the large-diameter pores of aerogel prepared by the ice template method, the pore diameter obtained by the vacuum filtration method is smaller, so more water transport channels are provided per unit area, and the smaller pore diameter further improves its capillary effect. The design of the internal pore structure of the aerogel provides a strong advantage for the application of the present invention in the field of interfacial evaporation.
[0146] It can be seen from the data in Table 1 and Table 2 that the evaporation rate stability of the aramid nanofiber-based carbon aerogel prepared in Example 1 is effectively improved compared with that in Comparative Example 3, and the evaporation rate is as high as 3.42 Kg / m 2 h. Combination Figure 3The reason is that the hydrophobic treatment effectively avoids the appearance of a clear water layer on the upper surface of the interface evaporator, and in the actual application process, it can ensure that the heat is effectively gathered at the gas-liquid interface, thereby improving the utilization efficiency of the heat. In addition, the presence of the hydrophobic layer on the upper surface can also effectively inhibit the salt precipitation at the interface, thereby increasing the service life of the product. The hydrophobic treatment provides a guarantee for the high efficiency of the present invention in actual application.
[0147] It can be seen from the data in Table 1 and Table 2 that the aramid nanofiber-based carbon aerogel prepared in Examples 1-7 has a smooth water vapor transmission channel, reasonable heat management capability, and efficient light-to-heat conversion capability through the design of its internal pore structure. And the use of aramid as a raw material and the hydrophobic treatment of the upper surface further improve its salt resistance and stability in practical applications. In summary, the aramid nanofiber-based carbon aerogel proposed in the present invention can be effectively used in the field of fresh water acquisition.
[0148] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing aramid nanofiber-based carbon aerogel, characterized in that: The following steps are involved: S1, dispersing aramid fibers in an alkaline solution, performing a deprotonation treatment, and dispersing to obtain a mixture containing aramid nanofibers; washing the mixture containing aramid nanofibers with deionized water to obtain an aramid nanofiber dispersion; S2, vacuum filtering the aramid dispersion and then freeze-drying it to obtain aramid nanofiber aerogel; S3, carbonizing the aramid nanofiber aerogel to obtain the aramid nanofiber-based carbonaceous aerogel.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the aramid dispersion in step S1 is 3-7 mg / mL.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the alkali to the co-solvent in the alkaline solution is (1-2) g:100 mL; the alkali is selected from one or more of potassium hydroxide and sodium hydroxide, and the co-solvent is selected from one or more of dimethyl sulfoxide, acetone, ethanol, methanol, tetrahydrofuran, acetonitrile, ethyl acetate, pyridine, glycerol, polyethylene glycol, and cyclohexane.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the aramid fiber to the alkali in step S1 is (0.1-0.5):1.
5.
5. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum filtration in step S2 is 0.01-0.1Mpa, and the pore size of the filter screen of the vacuum filtration is 400-600 mesh.
6. The preparation method according to claim 1, characterized in that: The freeze-drying temperature in step S2 is -40°C to 30°C, and the freeze-drying time is 60-80 hours.
7. The preparation method according to claim 1, characterized in that: The carbonization treatment in step S3 is carried out under an inert atmosphere, the temperature of the carbonization treatment is 700-1000° C., and the time of the carbonization treatment is 0.5-2 hours.
8. Aramid nanofiber-based carbon aerogel prepared by the preparation method according to any one of claims 1 to 7.
9. An interface evaporator, characterized in that: The interfacial evaporator comprises the aramid nanofiber-based carbon aerogel as described in claim 8, wherein the surface of the aramid nanofiber-based carbon aerogel in contact with the evaporating liquid is defined as a first surface, and the surface of the aramid nanofiber-based carbon aerogel away from the first surface is defined as a second surface, and the second surface is hydrophobically treated.
10. The interface evaporator according to claim 9, characterized in that The hydrophobic agent used in the hydrophobic treatment is selected from one or more of methyl perfluorododecanoate, perfluorooctane sulfonic acid, perfluorooctane carboxylic acid, perfluorononanoic acid, and perfluorohexane sulfonic acid.
Citation Information
Patent Citations
Expanded perlite-based aerogel structure solar interface evaporator and preparation method and application thereof
CN118047438A
Biomass-based carbon aerogel evaporator and preparation method and application thereof
CN118125540A
Cited By
Green low-temperature preparation method of nano aramid fiber aerogel based on bio-based solvent
CN121136185A
Aramid fiber 1414 / polyacrylonitrile nanofiber-based carbon aerogel and preparation method thereof
CN122424765A